A Review of Methodologies for Measuring Geogenic Rn Exhalation - Ouzounis, Athanasios; Kaissas, Ioannis (HNPS Advances in Nuclear Physics, 2025)
Radon (222Rn) and thoron (220Rn) are potential health hazards and therefore their concentration levels have been extensively monitored indoors across Europe resulting in indoor radon concentration maps [1]. Direct in situ measurements of geogenic radon and thoron exhalation are limited to a few locations worldwide while indoor measurements are more common. Potentially hazardous zones for long-term inhabitancy can be characterized, considering spatial geogenic radon exhalation data acquired before any construction activities. Furthermore, atmospheric simulations, earthquake prediction and identification of fractures within the lithosphere can be more accurate with the aid of radon exhalation data. In this review direct and indirect methodologies of measuring 222Rn and 220Rn exhalation are presented and compared.